Speaking difficulties of Philippine indigenous learners in English Semantics - J. Leaño, Adelaila; Mat Rabi, Norfishah; Gnana Piragasam, Grace Annammal (Southeast Asia Early Childhood Journal, 2019)
This study aimed to investigate Philippine indigenous learners’ speaking difficulties in English Semantics. The objectives was to identify indicators of poor vocabulary, processing and expressing of information. It was a qualitative research through case studies of five Grade 2 Indigenous Peoples (IP) learners in Echague, Isabela, Philippines. Data collection was done through observation and oral assessments activities. Instruments include checklist of speaking difficulties signified by inadequacy in English vocabulary; and constructed oral assessment activities in English. Data gathered were qualitatively analysed. Findings revealed that all the five indigenous learner-participants demonstrated English vocabulary deficiency to name depicted objects in the surroundings. They had struggles in reciting week-days, months and in citing common Philippine events. They had difficulty in conveying illustrated antonyms and synonyms. These findings denote a language intervention to improve essential skills in English semantics. This study can be an alternative to investigate problems in other language literacy domains.